Clinical Audit: Paediatric Medical Team Attendance at Deliveries in an Outer Metropolitan Hospital in Western Australia - Nadew, Gelaye Tadesse (International Journal of Medical Students, 2016)
Background: The attendance of paediatric medical teams at deliveries has become accepted as an integral part of birth management under current multidisciplinary team arrangements. Under current guidelines, specific clinical indicators have been developed to determine whether paediatric teams need to attend deliveries. High rates of attendance indicate that paediatric medical team resources are being extended beyond the criteria at the expense of essential services being provided elsewhere. Methods: A retrospective clinical audit was used to evaluate the frequency of paediatric team attendance and related clinical indicators. Deliveries were recorded and audited for a randomly selected calendar month. Paediatric team attendance was evaluated against foetal distresses, types of delivery, gestational age and birth weight. Results: A total of 112 deliveries were recorded for the selected calendar month and paediatric medical teams attended 74.1% (n=80) of the deliveries. Participants were comprised of 50.9% (n=57) male and 49.1% (n=55) female babies. Of these deliveries, 66.7% (n=72) were term, 30.6% (n=33) post-term and 2.8% (n=3) pre-term. A total of 69.4% (n=75) of deliveries were spontaneous vaginal deliveries (SVD), while 22.2% (n=24) were caesarean sections and 8.3% (n=9) were instrumental deliveries. Foetal distress was experienced by 16.2% (n=17) of babies. Conclusion: Paediatric medical team attendance at deliveries was higher than the combined rate of caesarean sections, pre-term babies, instrumental deliveries and reported cases of foetal distress.